(untitled) (Al-Academy, 2017)
The presence and absence binary is an essential part of and a motivation for the direction vision which depends on the principle that the components of the theatre performance move in contrast with each other; one is directly informative which is the presence relations and the other is structural that is identical to the absence relations. The first is material band visual that evokes the incorporeal mental absent. Hence, the present study(Presence and Absence in the Iraqi Theatre Performance :Summer’s Rain Play as an Example) aims at explaining those relations and their transformations between presence and absence in the performance